2019
DOI: 10.3390/su11143886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tourism Impact on the Socio-Economic Spheres of the Issyk-Kul Region (Kyrgyzstan)

Abstract: Based on the quantitative assessment methodology, the study examined the socio-economic impact of tourism in the region. The study proposed and tested on the example of the Issyk-Kul region, as it is the most visited region of Kyrgyzstan. Accordingly, economic and social efficiency was estimated by the integral indicators formed at the use of the weight coefficients calculated on the statistical data, and the forecast for tourism development in the region. The study showed that the impact of tourism on economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…In general, the findings of current study parallels to the past research (Almeida-García et al, 2016;Alrwajfah et al, 2019;Hengky, 2019;Kozak et al, 2006;Kozhokulov et al, 2019;McLoughlin et al, 2019;Smith, 2010).…”
Section: Table 2 -Reliability Test Scoresupporting
confidence: 90%
See 1 more Smart Citation
“…In general, the findings of current study parallels to the past research (Almeida-García et al, 2016;Alrwajfah et al, 2019;Hengky, 2019;Kozak et al, 2006;Kozhokulov et al, 2019;McLoughlin et al, 2019;Smith, 2010).…”
Section: Table 2 -Reliability Test Scoresupporting
confidence: 90%
“…Wesley and Pforr (2010) stated that tourism is specifically welcomed due to huge consumption of accommodation and foods. Great amount of tourist spending improve the local residents' income level together with community tax levels (Kozhokulov, Chen, Yang, Issanova, Samarkhanov and Aliyeva, 2019;Murray, 2007). Parallel to this, new efforts and developments in a destination to meet the demands of tourists and visitors provide more trade and production opportunities which expand the other sectors as well.…”
Section: Positive and Negative Economic Impact Of Coastal Tourismmentioning
confidence: 99%
“…The study by Kozhokulov et al (2019), also stated that there is a positive impact on the economic and social growth of the Issyk-Kul region, Kyrgyzstan due to tourism. The study found that the socio-economic impacts have grown marginally every year except for the years of political instability.…”
Section: Empirical Research Findingsmentioning
confidence: 97%
“…The percentage of these indicators can be seen in Figure 6. in the form of increased financing, product expansion, socio-economy, natural environment protection (Kumar et al, 2015;Kozhokulov et al, 2019;Zaei and Zaei, 2013).…”
Section: E Community Climate (Attitude and Support)mentioning
confidence: 99%